Electrocatalysis in confined spaces: interplay between well-defined materials and the microenvironment. Issue 3 (12th January 2021) - Han, Xue; Gao, Qiang; Yan, Zihao; Ji, Mengxia; Long, Christopher; Zhu, Huiyuan
Abstract : In this minireview, we summarize recent advances in electrocatalysis in confined spaces. Emerging electrochemical reactions are covered and discussed. Abstract : Catalysis in a confined space has attracted much attention due to the simultaneously designable nature of active sites and their microenvironment, leading to a broad spectrum of highly efficient chemical conversion schemes. Recent work has extended the scope of confined catalysis to electrochemical reactions. Mechanistic studies suggest that the confined environment in electrocatalysis can modulate mechanical, electronic, and geometric effects, stabilizing important charge-transfer intermediates and promoting reaction kinetics. In this minireview, we first discuss the fundamental concepts of confined catalysis by summarizing density functional theory (DFT) calculations and experimental investigations. We then present the rational design and applications of space-confined electrocatalysts with emphasis on the confined environment provided by carbon-based materials. We specifically focus on metal-based materials confined in carbon nanotubes (CNTs) and their applications in emerging electrochemical reactions including the oxygen reduction reaction (ORR), water-splitting reactions, carbon dioxide reduction reaction (CO2 RR), and nitrogen reduction reaction (NRR). Finally, the existing challenges, opportunities, and future directions of electrocatalysis in confined spaces are highlighted.